Theoretical study of the vibrational spectra of 2-chloropyridine metal complexes II. Calculation and analysis of the IR spectra of Cd– and Ni–2-Chloropyridine complexes - Bakiler, Meriç; Maslov, I. V.; AKYÜZ, SEVİM (Elsevier, 1999)
The vibrational IR spectra of a Cd complex of 2-chloropyridine, was calculated on the basis of a parameter set determined in our previous study on the 2-chloropyridine molecule. The Cd–N bond strength was determined by the variation of the force field, and the corresponding force constant is found to be (1.064 mdyne/Å). Calculated IR intensities indicate the presence of some changes in electron distribution of the 2Cl-pyridine molecule in a complex formation, with respect to the free molecule. The distortion of the electro-optical parameters occurs around the N atom. The interpretation of the normal vibrations and IR intensities of the Cd–2Cl-pyridine complex is given. Comparison with the corresponding shifts for the case of the Ni complex of 2Cl-pyridine, ensures that the force field of the free 2Cl-pyridine molecule should be altered in a complex formation, in order to represent experimental data.
Keywords: 2-Chloropyridine; IR spectrum; IR intensity; Force field refinement; Transition metal complexes